Relations between Peru and the United Kingdom. A testimony in 2025 - Higueras Hare, Ignacio (2025)
Starting with a reflection on three questions that help define its nature, the author offers an account of the state of bilateral relations between Peru and the United Kingdom in the year 2025. To this end, he combines three central elements: the content of the bilateral agenda, their national interests and, based on these, their shared interests, and the nature of the engagement between the two countries, all of which leads him to offer an assessment of these bilateral relations at present.